2016
DOI: 10.1038/srep34928
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and preliminarily environmental risk assessment of selected pharmaceuticals in the urban rivers, China

Abstract: Twelve selected pharmaceuticals including antibiotics, analgesics, antiepileptics and lipid regulators were analysed and detected in water samples collected from 18 sampling sections along the three main urban rivers in Yangpu District of Shanghai, China during four sampling campaigns. Besides, algal growth inhibition test was conducted to preliminarily assess the eco-toxicology induced by the target pharmaceuticals in the rivers. Mean levels for most of target compounds were generally below 100 ng/L at sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 36 publications
1
27
0
2
Order By: Relevance
“…While the occurrence of antibiotics in RW systems has been reported extensively ( Table 1 ), studies assessing their dissemination from HW are scarce. As highlighted in the current study, antibiotic concentrations found in RW were comparable to those found in China by Zhou et al [ 19 ]. When relating the antibiotic concentrations in RW and EW, studies [ 49 , 50 , 51 ] have reported that sublethal concentration of therapeutic antibiotics may select for antibiotic resistance in commensals and pathogenic microorganisms in the environment.…”
Section: Discussionsupporting
confidence: 90%
“…While the occurrence of antibiotics in RW systems has been reported extensively ( Table 1 ), studies assessing their dissemination from HW are scarce. As highlighted in the current study, antibiotic concentrations found in RW were comparable to those found in China by Zhou et al [ 19 ]. When relating the antibiotic concentrations in RW and EW, studies [ 49 , 50 , 51 ] have reported that sublethal concentration of therapeutic antibiotics may select for antibiotic resistance in commensals and pathogenic microorganisms in the environment.…”
Section: Discussionsupporting
confidence: 90%
“…Higher risk (RQ > 1) has been reported for Ibuprofen (6.43) in Kalpani river, Pakistan [86]. Zhou et al [87] reported lower risks levels (RQ < 1) for Ibuprofen, Diclofenac and Paracetamol in urban rivers in Shanghai, China. In contrast, a higher risk quotient was observed for Ibuprofen in the sediment of the Usuma Dam implying they constitute serious health threat to benthic and aquatic organisms in the dam (Table 5) .…”
Section: Ecological Risk Assessmentmentioning
confidence: 94%
“…All these compounds have significant effects on algal population density. Half maximal effective concentration (EC 50 ) values for these compounds vary between 0.026 and 100 mg/L (Petersen et al, 2014;Zhou et al, 2016). Pharmaceutical wastewater also contains heavy metals.…”
Section: Resultsmentioning
confidence: 99%